Regulation of salinity to inhibit 2-methylisoborneol and geosmin: Insights from spatial-scale research in coastal areas of China - Chen, Xi; Li, Zhonghua; Xu, Huimin; Qiu, Liping; Fan, Limin; Meng, Shunlong; Gao, Zexia; Song, Chao (Frontiers in Environmental Science, 2024)
Drinking water quality and the commercial value of aquatic items are both significantly impacted by odor molecules like 2-methylisoborneol (2-MIB) and geosmin (GSM). Many investigations have been conducted to identify the microorganisms involved in the synthesis of 2-MIB and GSM.However, few studies have attempted to identify potential degradation factors in the natural environment. Here, pathway analysis of the relationship between water quality parameters and the distribution of odor compounds in water bodies led to a more significant connection (P< 0.05) between total nitrogen, total phosphorus, chemical oxygen demand, and salinity in water bodies for the distribution of their odor compounds.Salinity among them exhibited the strongest connection and had a direct impact. The establishment of a larger spatial scale statistical research method, mainly using the water environment with different salinities formed in different geographical areas, and the distribution of odor compounds in this water body as a research vehicle helped to find the most concise relationship between the two variables. The results show that the concentration of odor compounds is lower in waters with higher salinity, which proves the negative correlation between the two. The results of this study provide a theoretical basis for solving the problem of odorous pollutants in water bodies, with the aim of improving the utilization of water resources more effectively and, secondly, leading to a new guiding direction for the conservation and exploitation of impact plains and mudflats.